PENGARUH KETERSEDIAAN PRODUK, EFISIENSI WAKTU, HARGA, DAN KENYAMANAN TERHADAP FREKWENSI PEMBELIAN PRODUK MELALUI INTERNET - Komari, Amat (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2005)
The purpose of the research is to figure out if such aspects as forms, times, process, and comfort influence the purchase frequency on products sold over the internet, in terms of individual purchace as well as the group one. Regression analysis it is found that the product availability, time efficiency, cost and comfort altogether influence the product purchasing frequency sold over internet. Individualy the product availability gives little influence to the non durable product purchasing frequency sold over internet. The time efficiency gives little influence to the non durable product purchasing frequency sold over internet, the price gives a strong influence to the non durable products purchasing frequency sold over internet), comfort gives strong influence to non durable products purchasing frequency sold over internet but it gives little influence to durable products purchasing frequency sold over internet), the product availability gives little influence to the durable products. the time efficiency gives little influence, The price gives strong influence.Keywords: Product, Price, Frequency, E-commerce